Thyroid function and thyroid autoantibodies in patients with chronic spontaneous urticaria - Czarnecka-Operacz, Magdalena; Sadowska-Przytocka, Anna; Jenerowicz, Dorota; Szeliga, Anna; Adamski, Zygmunt; Łącka, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Chronic urticaria (CU) is a skin disease caused by autoantibodies against high affinity immunoglobulin E (IgE) receptor and against IgE. It is characterized by hives, erythematous wheals and redness present minimum twice a week for at least 6 weeks. It is observed that there is a strong association between CU and autoimmune diseases, such as autoimmune thyroiditis (AT). Aim : To verify the frequency of AT in patients suffering from chronic spontaneous urticaria (CSU) and to confirm the coexistence of CU and AT in the Polish population. Material and methods : One hundred and forty-eight patients with CSU were included to the study. The presence of anti-thyroperoxydase antibodies (anti-TPO) and anti-thyroglobulin antibodies (anti-Tg) was checked and thyrotropin (TSH), free thyroxine (fT4) and free triiodothyronine (fT3) concentration was measured. Results were compared with outcomes in a group of 35 patients with no history of skin disease. Results : Thirty-three patients were diagnosed with AT. Frequency of elevated anti-TPO (p = 0.0045) and anti-Tg (p = 0.013) levels was much higher in patients with CU. A comparison of the current study and previous ones was conducted. In a group with CU, there was a higher risk of elevated anti-TPO (OR = 6.69) and anti-Tg (OR = 6.01) levels. Conclusions : There is a statistically significant difference in the presence of AT between the patients with CU and the whole population. Doctors should consider examining patients with CU for AT. Adequate therapy and guidance for patients could be implemented at an early stage of thyroid disease and help induce remission of skin disorders.